A novel design for concrete culverts absorbing explosive energy from homemade explosives - Savaş, Sedat; Bakır, Dursun; Başpınar, Muharrem; Ülker, Mehmet (Fırat University, 2022)
With the increasing number of terrorist attacks for the last 40 years, terrorist organizations have devised various attack tactics. One of these tactics is to attack by placing homemade explosives inside culverts that are originally constructed for draining water within road infrastructure. The aim of this study is to enable the absorption of the explosive blast in concrete culverts in face of homemade explosives. For this purpose, concrete culverts that were within three road embankments and road infrastructures were built by projects that were devised according to the American Association of State Highway and Transportation Officials Standards. The experiment was carried out in three stages. tjIn the first one of these culverts, a standard road was built. In the second and third culverts, a system that enabled the installation of secondary culverts above and below primary culverts was devised.In conclusion, it was revealed that the methods developed in the study could enable the absorption of the explosive energy of homemade explosives by 60%-80%.
Keywords: Civil Engineering; İnşaat Mühendisliği